Determination of Career Readiness of Prospective Economics Teachers in the Digital Era: Economic Behavior, Self-Efficacy, Social Support, Career Planning, and Career Motivation - Husnul Khotimah; Imam Mukhlis; Madziatul Churiyah (Green Publisher Indonesia, 2026)
The development of digital technology and the dynamics of the global job market demand an increase in the career readiness of graduates, especially prospective economics teachers. However, there is still a gap between the competencies of graduates and the needs of the world of work, which are influenced by factors of economic behavior, self-efficacy, social support, and career planning. This study aims to analyze the influence of these factors on career readiness with career motivation as a mediating variable. This study uses a quantitative approach with an explanatory method through the analysis of Structural Equation Modeling Partial Least Squares (SEM-PLS). The research sample amounted to 247 students of the Economics Education Study Program at three universities in Lampung Province. The results showed that economic behavior, self-efficacy, and career planning had a positive and significant effect on career readiness, while social support had no significant effect. In addition, self-efficacy, social support, and career planning have a significant effect on career motivation, but career motivation does not have a direct effect on career readiness and is unable to mediate the relationship between independent variables on career readiness. These findings confirm that career readiness is more influenced by real competencies, behavior, and strategic planning than motivational factors alone. This research makes a theoretical contribution to the development of Social Cognitive Career Theory (SCCT) as well as practical implications for the development of curriculum and career guidance programs in higher education.